2022
DOI: 10.32604/jrm.2021.016335
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Compatibility, and Balanced Regulation of the Mechanical, Thermal, and Antioxidant Activity of Polyvinyl Alcohol-Chinese Bayberry Tannin Extract Films Using Different Di-Aldehydes as Cross-Linkers

Abstract: Polyvinyl alcohol (PVA)-based films containing Chinese bayberry tannin (BT) were prepared by cross-linking using glyoxal, glutaraldehyde and dialdehyde starch, individually. The presence of cross-linkers was evident to promote the transparency and decrease the moisture content of PVA/BT films, while the water solubility stayed almost unchanged in the cross-linked PVA/BT films. All cross-linkers provided promotion of the water vapor permeability, mechanical property and thermal stability of PVA/BT films. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Afterwards, the TLP resin was put into a mold (10 × 10 × 1 cm 3 ), which was left to dry spontaneously over 1 h to obtain TLP film. In addition, PVOH [ 23 ], lignin/PVOH (LP) film and tannin/PVOH (TP) film were prepared under the same conditions for comparison with TLP film. The raw materials and amounts are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, the TLP resin was put into a mold (10 × 10 × 1 cm 3 ), which was left to dry spontaneously over 1 h to obtain TLP film. In addition, PVOH [ 23 ], lignin/PVOH (LP) film and tannin/PVOH (TP) film were prepared under the same conditions for comparison with TLP film. The raw materials and amounts are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…It is expected that adding tannin into PVA system can improve the tensile strength and hardness of the resulting film. However, due to the large steric hindrance, condensed tannins have poor reactivity with PVOH [ 22 ], and due to the large molecular weight of condensed tannins, they undergo agglomeration easily in PVOH, resulting in poor compatibility [ 23 ]. Therefore, in the case of the tannin and PVA system, a matrix with good adhesion properties is needed to uniformly fix the tannin in the PVA system during the mixing process.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the antioxidative and UV-protective properties of the tannin/PVA composite membrane were good, the potential of which is widely used in food packaging. Considering that tannins may be released from PVA, Liao and co-authors 161 prepared a PVA/ tannin (Chinese bayberry tannin (BT)) composite film by crosslinking using three types of aldehydes (glutaraldehyde, glyoxal, and dialdehyde starch) individually. Compared with the uncross-linked films, all the cross-linked PVA/BT displayed improved transparency, thermal stability, mechanical property, and water vapor permeability.…”
Section: Polyvinylidene Fluoride (Pvdf)mentioning
confidence: 99%
“…The radical scavenging assay of DPPH was studied to estimate the antioxidant activity as previously reported in our previous works [ 36 , 37 ]. Initially, 0.1 g of the tested sample was immersed in 30 mL of distilled water while magnetic stirring was applied for 30 min.…”
Section: Characterizationmentioning
confidence: 99%
“…Our previous studies have shown that Chinese bayberry tannin (BT) presented a good antioxidant function of BT incorporated into PVA films [ 36 , 37 ]. However, the imperfect miscibility and weak covalent bonds of two components were generally found, even with the help of aldehydes, due to the large molecular weight of BT, which makes its incorporation into PVA more difficult compared with other polyphenols.…”
Section: Introductionmentioning
confidence: 99%